PENGEMBANGAN MEDIA LAGU UNTUK PENGHAFALAN KOSAKATA BAHASA JEPANG - Karina Purnama Sari; Hadriana Hadriana; Hana Nimashita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstrak: This study describes research and development of the song for student help to learn Japanese vocabulary. The menthod is able for self-study, learning and memorizing vocabulary by the song. This study aims to help if research and development menthod is suitable by the standar of the expert/validator for class learning. The procedures are 1) potential background, 2) data-collecting, 3) planning, 4) product development, 5) validation, and 6) product revision. Data-collecting methods are distributes the questionnaire then collects the result done by media and material experts/validators. The validation results of the songs are Doraemon song received 80% of material and 91,6% of media, Ninja Hatori song received 79,1% of material and 91,6% of media, and P-Man song received 87,5% of material and 66,6% of media, the three songs are suitable for learning and memorizing the vocabulary words.Key Words: media-learning, song, vocabulary, research and development